Long-term Effects of Irrigation with Treated Municipal Wastewater on Soil Chemical and Physical Responses in Commercial Vineyards in the Coastal Region of South Africa - Hoogendijk, K.; Myburgh, P.A.; Howell, C.L.; Lategan, E.L.; Hoffman, J.E. (South African Journal of Enology and Viticulture, 2024)
The prolonged drought in the Western Cape province of South Africa in recent years has been particularly detrimental to the wine industry. Water restrictions imposed by authorities and the limited supply of fresh water that can be stored, have emphasisedthe need for alternative water sources for vineyard irrigation. Treated municipal wastewater has been used successfully as an alternative source of irrigation water in other countries. A long-term trial was conducted in commercial vineyards in the Coastal region of South Africa to assess the impact of treated municipal wastewater irrigation on vineyards. Cabernet Sauvignon and Sauvignon blanc grapevines were irrigated using treated municipal wastewater from the Potsdam wastewater treatment works for 11 years. Grapevines were either rainfed (RF), irrigated with treated municipal wastewater via a single dripper line (SLD), or received twice the volume of wastewater via a double dripper line (DLD). Irrigation using treated municipal wastewater increased soil pH(KCl), the electrical conductivity of the saturated extract (ECe) and Cl-. Substantial amounts of Na+ and K+ accumulated in the topsoil due to irrigation with treated municipal wastewater. These soil K+ increases could have a negative effect on wine colour stability should the levels of soil K+ be such that they are absorbed excessively by grapevines. The near-saturation hydraulic conductivity (Kns) at the surface of the soil could be related to the ECe in the topsoil. The results represent specific in-field situations in three commercial vineyards under one set of climatic conditions.